2017
DOI: 10.1111/tbed.12737
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and comparison of diagnostic tests for characterization of foot‐and‐mouth disease virus strains from Pakistan 2008–2012

Abstract: We report the laboratory analysis of 125 clinical samples from suspected cases of foot-and-mouth disease (FMD) in cattle and Asian buffalo collected in Pakistan between 2008 and 2012. Of these samples, 89 were found to contain viral RNA by rRT-PCR, of which 88 were also found to contain infectious FMD virus (FMDV) by virus isolation (VI), with strong correlation between these tests (κ = 0.96). Samples that were VI-positive were serotyped by antigen detection ELISA (Ag-ELISA) and VP1 sequence acquisition and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 60 publications
(86 reference statements)
3
12
0
Order By: Relevance
“…Furthermore, we are reporting the regional co‐circulation of multiple serotypes of FMDV in the districts of Kyankwanzi, Kiruhura and Nakasongola. This is consistent with the previous reports from other endemic countries situated on the Asia and Africa continents (Ahmed et al, ; Brito, Rodriguez, Hammond, Pinto, & Perez, ; Di Nardo, Knowles, & Paton, ; Tekleghiorghis et al, ), and might represent a potential risk for the emergence of new strains in Uganda, considering the ability of FMDV to evolve by interserotypic recombination (Balinda, Belsham, et al, ; Carrillo et al, ). Circulation of FMDV in Uganda was evidenced by the high proportion of herds (82.6%) with antibodies against NSPs during this study.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we are reporting the regional co‐circulation of multiple serotypes of FMDV in the districts of Kyankwanzi, Kiruhura and Nakasongola. This is consistent with the previous reports from other endemic countries situated on the Asia and Africa continents (Ahmed et al, ; Brito, Rodriguez, Hammond, Pinto, & Perez, ; Di Nardo, Knowles, & Paton, ; Tekleghiorghis et al, ), and might represent a potential risk for the emergence of new strains in Uganda, considering the ability of FMDV to evolve by interserotypic recombination (Balinda, Belsham, et al, ; Carrillo et al, ). Circulation of FMDV in Uganda was evidenced by the high proportion of herds (82.6%) with antibodies against NSPs during this study.…”
Section: Discussionsupporting
confidence: 92%
“…During the current study period, the most prevalent FMDV serotype isolated was Asia‐1, followed by serotypes A, and O. The dominance of serotype Asia‐1 in infected animals is consistent with recent work from our laboratory which characterized outbreak viruses in overlapping geotemporal space (Ahmed et al., ). These findings contrast earlier works which reported serotype O as the most prevalent serotype, followed by A, then Asia‐1 (Abubakar, Arshed, Ali, & Hussain, ; Jamal et al., ; Waheed et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…Four distinct clusters of Asia‐1 isolates were identified across the study with multiple clusters identified within individual farms, and in three instances within individual animals. The majority of these FMDV Asia‐1 isolates were closely related to reference isolates collected in ICT and Rawalpindi, which is consistent with the extensive livestock movement between these cities (Ahmed et al., ; Barros et al., ). The high prevalence and diversity of Asia‐1 strains recovered in the current study suggests that this serotype was circulating subclinically in Pakistan during 2011–2012.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous studies have shown a higher sensitivity of PCR compared to VI (14, 56, 57), and the results of the current study may reflect similar differences in sensitivity. However, other studies have reported similar sensitivities for PCR and VI (58). Overall, multiple biological and artefactual phenomena may contribute to the relative efficacies of viral detection by rRT-PCR and VI.…”
Section: Discussionmentioning
confidence: 74%